Preparation and Evaluation of Dietetic Cookies for Vulnerable Segments Using Black Cumin Fixed Oil - Sultan, M. Tauseef; Butt, Masood Sadiq; Pasha, Imran; Qayyum, Mir M. Nasir; Saeed, Farhan; Ahmad, Waqas (Pakistan Journal of Nutrition, 2011)
Varying consumption trends and poor dietary habits had led to widespread prevalence of various lifestyles related disorders including obesity, diabetes and dyslipidemia. The reliance of communities on processed foods is also detrimental factor in their progression. The concerted efforts are required in order to eliminate these problems. In this project, efforts were directed to prepare nutritious dietetic cookies using Black Cumin Fixed Oil (BCFO). Accordingly, formulations of cookies were modified to reduce the fats, sugar and energy level along with provision of some bioactive molecules from BCFO. The results indicated that reduction in fat and sugar levels provided less calorific value to cookies. However, utilization of BCFO (~4%) resulted in some quality retention even at reduced levels of fats and sugars. Furthermore, reducing the level of shortening and sugars resulted in decreased fat contents (45.61%) as compared to control. Similarly, total sugar levels were decreased by 43.17%. These cumulative factors led to dwindled calorific value by 37.98%. The reduction in fats and sugars led to decreased sensory appraisal from trained taste panel. However, at 40% reduction in fats and sugars were quite acceptable owing to presence of BCFO. It further provided protection against lipid per-oxidation as indicated from peroxide value. In the nutshell, preparation of nutritious and dietetic cookies using BCFO is feasible approach to reduce the calorific value of cookies and such novel products hold potential to reduce the obesity and related disorders.